Analisis Faktor-Faktor yang Mempengaruhi Tingkat Akurasi Perkiraan Biaya Awal pada Tahap Konstruksi (Persepsi Kontraktor di kota Jambi) - Hasanah, Uswatun; Yamali, Fakhrul Rozi; Dwiretnani, Annisaa (Jurnal Talenta Sipil, 2025)
Making a budget or cost estimate is part or project planning. The financial benefits that the constractor and project owner will receive depend on their level of axpertise in estimating the project cost.This research aims to identify which factors moast influence the level of accuracy of initial cost estimates at he construction stage and to find out how much influence these factors have on the level of accuracy of cost estimates. Primary data collection technique with asample of 14 respondents taken from the perceptions of contractors in jambi. The sampling technique in this research used the total sampling method. Data analysis processing in this research used microsoft excel 2010. The research result found that the factor that most influences the level of accuracy of initial cost estimates at the construction stage is the availability of data and information regarding the project with a mean value obtained 4,00 , the second factor is the technique or method used with amean value of 3,82 , the third factor is the skill and experience of the estimator with a mean value of 3,79 , and the fourth factor is the purpose of using the cost estimate with a mean value 3,40.